Manipulative nature of translation: interpretators and interpretations - Garnyk, Liudmyla Petrivna; Vitkovskyi, Yurii (My University, 2021)
The article provides critical examination of manipulation as multidimensional phenomenon related with translation and interpreting in light of assurance of informational safety that is our research object. Research methodology is based on critical analysis of manipulations with texts and proficiency requirements for translator. Results of our research are corresponding to theory and practice of translation, psychology, comparative religious studies and national security. Practical value of obtained results consists in proposed algorithms for critical analysis of translated or interpreted texts that allows to evaluate their quality according to context, meaning and semiotics of original ones.
Keywords: translation; interpretation; consciental war; informational security; manipulations; cross-cultural communication; management